2010
DOI: 10.18388/abp.2010_2399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of medicinal plants containing polyphenol compounds. Comparison of two extraction systems.

Abstract: This study investigates the influence of extraction system on the extractability of polyphenol compounds and antioxidant activity of various medicinal plants. Oxygen radical absorbance capacity (ORAC) and total polyphenol content of 25 Bulgarian medicinal plants subjected to water or 80 % acetone extractions were investigated and compared. The type of extragent significantly influenced the efficiency of the polyphenol extraction and the antioxidant activity. In all cases ORAC results and total polyphenol conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
4
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 33 publications
(38 reference statements)
6
66
4
8
Order By: Relevance
“…It is possible that after the protein is hydrolysed by pepsin or trypsin, the polyphenols that are covalently or noncovalently bound to the protein may be released. However, the amount of polyphenols does not represent a potential synergistic or antagonistic effect among the compounds in the sample, depending on their structure and interaction (Kratchanova et al ., ). This study found that the antioxidant activity of phenolic compounds may decrease after interacting with protein.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that after the protein is hydrolysed by pepsin or trypsin, the polyphenols that are covalently or noncovalently bound to the protein may be released. However, the amount of polyphenols does not represent a potential synergistic or antagonistic effect among the compounds in the sample, depending on their structure and interaction (Kratchanova et al ., ). This study found that the antioxidant activity of phenolic compounds may decrease after interacting with protein.…”
Section: Discussionmentioning
confidence: 97%
“…Thyme aqueous extract was prepared by standard method of aqueous extraction as follows (Komes et al, ; Kratchanova, Denev, Ciz, Lojek, & Mihailov, ): 10 g of dried thyme (Institute of Medicinal Plants Research Dr Josif Pancic, Serbia) was extracted with distilled water (200 mL) at 80–100°C. It was constantly stirred under heating for a period of 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Thyme aqueous extract was prepared by standard method of aqueous extraction as follows (Komes et al, 2010;Kratchanova, Denev, Ciz, Lojek, & Mihailov, 2010)…”
Section: Preparation Of Thyme Extractmentioning
confidence: 99%
“…The extract of Centella asiatica possesses confirmed antioxidant, cognitiveenhancing, antiepileptic, antinociceptive and anti-inflammatory properties [28,29]. Free radical scavenging activity of Melilotus officinalis was confirmed in ORAC (Oxygen radical absorbance capacity) [30]. In turn Hippophae rhamnoides has the ability to scavenge peroxyl radicals and to protect against UV radiation.…”
Section: Introductionmentioning
confidence: 92%